Необхідність використання сучасної рекламної діяльності в системі маркетингу - Румянцева, Вікторія; Морушко, Олександр (Видавництво Львівської політехніки, 2020)
The article considers the relevance of the advertising campaign, the need to use it. The basic interpretations of the term “advertising” are defined. Formed advertising functions.
Keywords: реклама; маркетинг; функції реклами; комунікація